AFFECTING FACTORS FARMER WELFARE IN INDONESIA - Maridjo, Herry; Mudayen, Yohanes Maria Vianey (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to analyze the factors influencing the economic welfare of farmer households in Indonesia, focusing on the impact of arable land area, total production costs, labor allocation, and the percentage of land ownership. The research also seeks to specify the agricultural household economic model and propose alternative policy measures to enhance farmer welfare. Utilizing data from the Indonesian Family Life Survey (IFLS), the study employs Ordinary Least Squares (OLS) and Fixed Effect panel data models for analysis. The findings reveal that larger arable land areas, increased workload, and higher percentages of owned land significantly improve national farming income, thereby enhancing farmer welfare. Conversely, higher total production costs negatively impact welfare levels in both upland and rice field contexts. The economic model's specifications across eight structural equations align well with theoretical expectations, indicating robustness and consistency with observed agricultural phenomena. Policy simulations suggest that promoting employment opportunities in the off-farm sector could be an effective strategy to boost farmer welfare. Such policies may lead to a reduction in labor allocated to agriculture, increased overall household income, higher expenditures on food consumption from agricultural outputs, and an expanded household income surplus. These findings provide valuable insights for policymakers aiming to formulate targeted interventions that address the challenges faced by farmers, ultimately improving their economic well-being and ensuring sustainable agricultural development in Indonesia.